Influence of Academic Qualification on Employment in Hotels. A Critical Literature Review - Mutuku, Caren Waithera (Journal of Modern Hospitality, 2022)
Purpose: The hospitality industry is one of the largest employers and among the highest revenue earners in Kenya. The overall objective of this study was to examine influence of parent attitude toward consumption of sugary products by their children. Methodology: The paper used a desk study review methodology where relevant empirical literature was reviewed to identify main themes and to extract knowledge gaps. Findings: This study concluded that established that frequency of consumption of Sugar products varies depending on the type of beverage, and that overall, the more than half of the students' surveyed reported consuming high amounts of sugar-sweetened beverages. Observations from the study showed that energy drinks were the least consumed while sugar-sweetened beverages like tea, coffee and cocoa were the most highly consumed sugary products. By volume, 300ml packing was most preferred by all respondents across all classes of study. Moderate nutritional knowledge on possible effects of sugary products such as weight gain and dental erosion was observed among respondents. Unique Contribution to Theory, Policy and Practice: This study recommended that the ministry of health in conjunction with the ministry of education to incorporate nutritional literacy in the education programs both to the parents and the children to be aware of the demerits of consuming sugary products. This will also contribute to change in attitude and eventually change in behavior.